Identification of Novel Components of the Unfolded Protein Response in Arabidopsis - Hossain, Md. Amir; Henríquez-Valencia, Carlos; Gómez-Páez, Marcela; Medina, Joaquín; Orellana, Ariel; Vicente-Carbajosa, Jesús; Zouhar, Jan (Frontiers in Plant Science, 2016)
Unfavorable environmental and developmental conditions may cause disturbances in protein folding in the endoplasmic reticulum (ER) that are recognized and counteracted by components of the Unfolded Protein Response (UPR) signaling pathways. The early cellular responses include transcriptional changes to increase the folding and processing capacity of the ER. In this study, we systematically screened a collection of inducible transgenic Arabidopsis plants expressing a library of transcription factors for resistance towards UPR-inducing chemicals. We identified 23 candidate genes that may function as novel regulators of the unfolded protein response and of which only three genes (bZIP10, TBF1 and NF-YB3) were previously associated with the UPR. The putative role of identified candidate genes in the UPR signaling is supported by favorable expression patterns in both developmental and stress transcriptional analyses. We demonstrated that WRKY75 is a genuine regulator of the ER-stress cellular responses as its expression was found to be directly responding to ER stress-inducing chemicals. In addition, transgenic Arabidopsis plants expressing WRKY75 showed resistance towards salt stress, connecting abiotic and ER-stress responses.